Air-Conditioning and the Transmission of COVID-19 in Indoor Environment - Oye, Tosin T.; Gupta, Edinburgh Napier University; Goh, Keng; Oye, Toyosi K. (Environmental Management and Sustainable Development, 2021)
Substandard ventilation in restricted air-conditioning indoor places is allied with upsurge in the respiratory infections’ transmission. There have been several COVID-19 spread occurrences connected with indoor environment, together with a few from pre-symptomatic situations. Ventilation role in averting coronavirus transmission is not precise (i.e., through inhibiting transmission of an infectious dose to susceptible individuals or preventing the spreading of contagious particles to lessen the risk of transmission). SARS-CoV-2 is believed to be mainly spread through significant respiratory droplets, nevertheless, a growing amount of epidemic information associate aerosol role in the epidemics of coronavirus. Aerosols comprise of droplet nuclei and little droplets which stay in the air for longer than significant droplets. Recent studies show that coronavirus particles can stay transmissible on numerous substances, including aerosols within the indoor environments, as well as the contagion period contingent on humidity and temperature. Thus far, COVID-19 transmission via air-conditioning systems is unclear, but it is considered possible.